2019
DOI: 10.1186/s13046-019-1424-4
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin derivative WZ35 inhibits tumor cell growth via ROS-YAP-JNK signaling pathway in breast cancer

Abstract: BackgroundBreast cancer is the most prevalent cancer among women worldwide. WZ35, an analog of curcumin, has been demonstrated to remarkably improve the pharmacokinetic profiles in vivo compared with curcumin. WZ35 exhibits promising antitumor activity in gastric cancer, HCC, colon cancer. However, antitumor effects of WZ35 in breast cancer and its underlying molecular mechanisms remain unclear.MethodsCCK8, Flow cytometry and transwell assays were used to measure cell proliferation, cell cycle arrest, apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 54 publications
3
69
0
Order By: Relevance
“…Current study presents that activation of the p38 and JNK can lead apoptotic effect in MCF-7 cells. The pathway is consistent with the route suggested by previous researches [21,53,[75][76][77][78][79][80][81]. Numerous natural products show anticancer activity by the cooperation and/or downstream the signals transduction of p38 and JNK, accompanying the apoptotic effect.…”
Section: Discussionsupporting
confidence: 90%
“…Current study presents that activation of the p38 and JNK can lead apoptotic effect in MCF-7 cells. The pathway is consistent with the route suggested by previous researches [21,53,[75][76][77][78][79][80][81]. Numerous natural products show anticancer activity by the cooperation and/or downstream the signals transduction of p38 and JNK, accompanying the apoptotic effect.…”
Section: Discussionsupporting
confidence: 90%
“…7). The present study revealed that the protein expression levels of YAP were decreased in the combination group, and previous studies have demonstrated that YAP is associated with the occurrence of breast cancer (69)(70)(71). YAP can enhance cell growth and tumor growth (72,73).…”
Section: Discussionsupporting
confidence: 80%
“…Recurrence and chemoresistance have restricted the efficacy of currently applied treatment in breast cancer therapy [ 97 , 98 , 99 , 100 ]. Natural products have demonstrated an excellent inhibitory effect on both proliferation and metastasis of breast cancer [ 101 , 102 , 103 , 104 ]. A combination of chrysin and silibinin is beneficial in suppressing breast cancer malignancy via decreasing cancer proliferation.…”
Section: Chrysin and Cancermentioning
confidence: 99%